Measurement of Supermarket Service Quality by Applying Simple Content Analysis on Tweets - Anandianto, Rahadian; Iskandar, Budi Permadi (The Indonesian Journal of Business Administration, 2012)
Competition in the retail industry means that any company trying to attract consumers to buy products in stores with the attention to the retail marketing mix. In addition to competitive factors, the number of consumer and public complaints about retail marketing mix noted for improve quality of care. Social media as a two-way communication between a brand with consumers and public is the right analysis tool for use to understanding it. So, the purpose of this study was to evaluate the retail services in Bandung by using criteria based on service marketing mix of consumer and public opinion through social media. To understand of complaints, researcher use content analysis to identification the needs of consumer through sentiment. As a new tool analysis, Twitter can be used to explore service quality of retail. The main analysis is see the advantages and disadvantages of marketing mix in serving consumer through the division between the marketing mix with a number of conversations for each sentiment. The smaller the value indicates the most important marketing mix for repair. After run the analysis, the general weaknesses of retail are price, process, and people. All weaknesses in each retail must consider for management to increase satisfaction and loyalty of consumers. Keywords: marketing mix, retail service, content analysis, Twitter, conversation